2017
DOI: 10.1111/pce.12898
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variations and differential expressions detected at quantitative trait loci for salt stress tolerance in wheat

Abstract: The increasing salinization of agricultural lands is a threat to global wheat production. Understanding of the mechanistic basis of salt tolerance (ST) is essential for developing breeding and selection strategies that would allow for increased wheat production under saline conditions to meet the increasing global demand. We used a set that consists of 150 internationally derived winter and facultative wheat cultivars genotyped with a 90K SNP chip and phenotyped for STacross three growth stages and for ionic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 89 publications
5
111
1
Order By: Relevance
“…On the other hand, in the study by M.K. Turner et al (2017), it was shown that smaller panels might allow for detection of false negative associations that would not have been detected in more extensive panels (Oyiga et al, 2017). Therefore, the results of this study using relatively small soybean collection size (n = 182) may potentially relate to the above-mentioned findings by M.K.…”
Section: Discussioncontrasting
confidence: 44%
“…On the other hand, in the study by M.K. Turner et al (2017), it was shown that smaller panels might allow for detection of false negative associations that would not have been detected in more extensive panels (Oyiga et al, 2017). Therefore, the results of this study using relatively small soybean collection size (n = 182) may potentially relate to the above-mentioned findings by M.K.…”
Section: Discussioncontrasting
confidence: 44%
“…To unravel candidate QTGs that might contain alleles controlling salt stress-related traits, salt-4 0 0 responsive transcripts within the LD blocks harboring markers with significant phenotypic 4 0 1 effect were identified and analyzed. The Table 3 presents the candidate QTGs from two QTL 4 0 2 identified in an association panel (Oyiga et al, 2018) and an AB-QTL mapping population (Table 3). Among them, TraesCS2A02G395000 showed the strongest stress response in other abiotic stress studies for the four candidate QTGs determined in both intervals (Table 4 1 6 3).…”
Section: 8mentioning
confidence: 99%
“…Therefore, this gene is a strong 5 3 9 candidate that can be prioritized for further validation analyses. The AB-QTL mapping Wang et al (2014) b From mapping study (Oyiga et al, 2018) c From mapping study (Dadshani, 2018) d GFOLD values from tolerant genotypes are bold and from the susceptible are in italics. e Based on the Interpro results from the RefSeqv1.0 annotation (Alaux et al, 2018).…”
Section: 8mentioning
confidence: 99%
“…QTL [30,71,182,189,[201][202][203][204][205][206][207], and durum wheat [41, 73, [211][212][213]. When QTL have been discovered, one approach is to then identify the gene in that region of DNA, which is responsible for the salt tolerance phenotype.…”
Section: Exploitation Of Natural Variationmentioning
confidence: 99%